Synergetic computers and cognition a top-down approach to neural nets - Haken H (Berlin Springer-Verlag, 2004)
This book presents a novel approach to neural nets and thus offers a genuine alternative to the hitherto known neuro-computers. The new edition includes a section on transformation properties of the equations of the synergetic computer and on the invarian
Keywords: Neural networks